Linaria argillicola (Plantaginaceae), a new species of L. sect. Supinae from the southern Iberian Peninsula - Juan, Ana; Blanca, Gabriel; Cueto, Miguel; Fuentes, Julián; Sáez, Llorenç (Phytotaxa, 2018)
A new species of the genus Linaria is described, illustrated and compared with its morphologically closest relatives from L. sect. Supinae: L. accitensis, L. aeruginea, L. tristis and L. badalii. A principal component analysis (PCA), correspondence analysis (CA), and linear discriminant analysis (LDA) were carried out for morphological differentiation. The species is characterized by long abaxial sepals, corolla mostly yellow or rarely reddish with wide tube, wide winged seeds with a tuberculate seminal disc, and a non-continuous fruiting inflorescence. Linaria argillicola is an edapho-endemic species, growing on the marly gypsiferous deposits from the Guadiana Menor river basin, on the border of Granada and Jaén provinces (Andalusia, Spain).